Window optimization enabling broadband double-layer antireflection coating for GaAsP/SiGe tandem on silicon. (April 2016) - Conrad, Brianna; Zhao, Xin; Li, Dun; Wang, Li; Diaz, Martin; Soeriyadi, Anastasia; Lochtefeld, Anthony; Gerger, Andrew; Barnett, Allen; Perez-Wurfl, Ivan
Highlights: A double-layer ARC is designed for tandem cells with spectral response up to 1400 nm. The window layer thickness is optimized at the same time for maximum current. Collection of carriers generated in the window is observed and included in design. The difference in performance from a triple-layer coating is halved. Window optimization is shown to also improve DARC performance on 4-junction cells. Abstract: A high-performance broadband double-layer antireflection coating (DARC) is designed for GaAsP/SiGe tandem solar cells on a silicon substrate. Optimization of the window layer as part of the ARC design allows lower reflection to be achieved across the full range of the device's spectral response. Previous work has rarely fully optimized the window in DARC designs. An estimated non-zero collection profile from the window layer is used in optimization. Variation of the exact collection profile has minimal impact on the ideal design. DARC designs which result in currents within 1% of similarly optimized triple-layer designs, without the need for increased complexity in fabrication, are achieved. The benefit of an optimized window used with DARC is shown to apply also to 4-junction cells.